Volatile organic compounds from Italian vegetation and their interaction with ozone. - Calfapietra, Carlo; Fares, Silvano; Loreto, Francesco (Environmental pollution (Barking, Essex : 1987), 2009)
Volatile Organic Compounds (VOCs) emitted from vegetation (particularly isoprenoids) represent an important source of atmospheric hydrocarbons almost double the anthropogenic source. When biogenic VOC mix with NO(x) in the presence of UV radiation, ozone (O(3)) is formed. In Italy, optimal conditions for O(3) formation in terms of VOC/NO(x) ratios and abundance of UV radiation occur for long periods of the year. Moreover, Italian vegetation includes several species that are strong and evergreen isoprenoid emitters, and high temperatures for part of the year further stimulate these temperature-dependent emissions. We review emission of isoprenoids from Italian vegetation, current knowledge on the impact of rising O(3) levels on isoprenoid emission, and evidence showing that isoprenoids can increase both the O(3) flux to the plant and protection against oxidative stress because of their antioxidant functions. This trait not only influences plant tolerance to O(3) but also may substantially alter the flux of O(3) between atmosphere and biosphere.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 19019511
Keywords: antioxidant; isoprene; Monoterpene; Ozone flux; VOC